Context in Didactic Conception of Physics Education - Dzerviniks, Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article offers an evaluation of the concept “Context”, discloses the role and opportunities of contexts for the improvement of physics learning process, as well as provides with the theoretical justification for context-oriented approach. The objective of the article is to evaluate inclusion of the context and context-oriented approach into didactic conception of physics education. In the research which is discussed in the article, scientific literature is analyzed; analytical judgments are based on the previous researches, as well as on the personal pedagogical experience of the author.